Cropping System and Rotational Grazing Effects on Soil Fertility and Enzymatic Activity in an Integrated Organic Crop-Livestock System - Galindo, Fernando Shintate [UNESP]; Delate, Kathleen; Heins, Bradley; Phillips, Hannah; Smith, Andrew; Pagliari, Paulo Humberto (Mdpi, 2020)
Alternative grazing systems that incorporate cover crops may be useful to achieve a longer grazing season and maximize forage production. However, little is known about their impact on soil properties, especially in the presence or absence of cattle grazing in the early spring. The aim of this study was to evaluate the interacting effects of cropping systems with and without cattle grazing in rotation with corn or soybean on the balance and dynamics of soil fertility and enzyme activity. This study was conducted as a system experiment between 2015 and 2019 in Minnesota and Pennsylvania, USA. The experimental design was a randomized complete block design with four replications. Treatments included presence or absence of cattle grazing and two types of cropping systems (pasture-rye-soybean-pasture [P-R-SB-P] and pasture-wheat/vetch-corn-pasture [P-W/V-C-P]. Soil samples were collected six times during the study. Soil properties analyzed were soil pH, organic matter, salinity, K, Ca, Mg, cation exchange capacity (CEC), P, beta-glucosidase, alkaline phosphatase, aryl-sulfatase, fluorescein diacetate hydrolysis, ammonium, nitrate, permanganate oxidizable carbon (POXC), N%, C%, S%, and C:N ratio. Grazing increased glucosidase activity, available Ca, Mg, NO3-, NH4+, soil pH, soil C%, S%, and the C:N ratio. In the P-W/V-C-P cropping system, soil pH, available Ca, NO3-, and sulfatase activity were found to increase compared with the P-R-SB-P cropping system. In contrast, soil OM, available K, Mg, CEC, glucosidase, phosphatase, POXC, and total C%, N%, and S% were greater in the P-R-SB-P cropping system compared with the P-W/V-C-P cropping system. The results of this study suggested that rotational grazing can increase soil quality and microbial decomposition under the P-W/V-C-P cropping system, and that this result was greater than under the P-R-SB-P cropping system, leading to a faster nutrient cycling. These results show promise for producers who are seeking methods to diversify their farming operation and reduce the need for external inputs.
Keywords: cattle grazing; conservation agriculture; cover crops; organic cropping systems; soil quality